2021
DOI: 10.4103/2347-5625.308678
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Care and Perceived Psycho-Social Outcomes among Family Caregivers of Patients Living with Cancer

Abstract: Objective: Caring for patients living with cancer requires the support of family caregivers. Literature reports experiences of diverse burdens and health effects among caregivers. This study examined the burden, physical, psycho-social, and financial outcomes of caregiving among caregivers of patients living with cancer. Methods: This cross-sectional descriptive study was conducted in the University College Hospital, Ibadan, Nigeria, between January and March 2019. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Education on achieving a work-life-caregiving balance, could help FCCs learn to balance their time, manage their roles, and attend to their self-care [ 43 ]. Next, clinicians could also informally assess how the caregiver is coping during patient consultations, so that their needs are recognised and addressed [ 44 ]. Studies however have shown that although interventions and social support already exist, and FCC express interest in utilizing these many actually do not avail themselves of the services [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education on achieving a work-life-caregiving balance, could help FCCs learn to balance their time, manage their roles, and attend to their self-care [ 43 ]. Next, clinicians could also informally assess how the caregiver is coping during patient consultations, so that their needs are recognised and addressed [ 44 ]. Studies however have shown that although interventions and social support already exist, and FCC express interest in utilizing these many actually do not avail themselves of the services [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing incidence of new cancer cases in recent years, the number of people undertaking cancer caregiver roles has been on the rise dramatically (Onyeneho and Ilesanmi, 2021 ). A remarkable proportion of caregivers are the family members of patients with cancer, who play a noteworthy role in assisting their patients to confront the harsh reality of cancer diagnosis and equip them with both practical and emotional support (Onyeneho and Ilesanmi, 2021 ). Following the diagnosis of cancer and initiating the treatment process, the patient's family members feel responsible for taking care of their patient.…”
Section: Introductionmentioning
confidence: 99%
“…Using the 10 outcome events per predictor variable (EPV) rule and considering a 70% prevalence of CB using the ZBI-22 cutoff score of 21 [ 20 24 ], at least 214 participants were needed for logistic regression analysis including 15 predictor variables. Anticipating a 10% exclusion rate, the sample size was further increased to 236 participants.…”
Section: Methodsmentioning
confidence: 99%